Status of AnGR of Maharashtra in 19th century: A review - Bankar, P.S.; Patil, Snehal; Kuralkar, S.V.; Chopade, M.M.; Jadhav, P.V. (Journal of Livestock Biodiversity, 2025)
Maharashtra, India’s second-most populous and third-largest state, is rich in domestic animal biodiversity, contributing significantly to the country’s agricultural economy. With a population of 112 million and diverse geographical features, ranging from the Konkan coast to the Sahyadri mountains and the Deccan Plateau, the state supports varied agroclimatic zones. Approximately 25% of its population is engaged in farming, with livestock contributing around 7% to the national total. Key breeds include Dangi and Deoni cattle, Nagpuri buffaloes, Osmanabadi goats, and Deccani sheep, showcasing a wide genetic diversity. The state’s history of animal husbandry dates back to the British colonial era, when various cattle breeds were categorized based on their regions, and many were imported for agricultural purposes. Despite facing challenges such as climate variability and fodder scarcity, efforts like the Indian government’s “Mission Zero Non Descript” aim to document and enhance non-descript genetic resources. Historical records reveal extensive livestock diversity and highlight the importance of understanding past practices to inform current animal breeding strategies. This review underscores the need for a comprehensive understanding of Maharashtra’s livestock heritage to promote sustainable agriculture and biodiversity conservation.